Recipe for disaster - Fergus, Maureen (KCP Fiction, 2009)
Francine's nearly perfect life begins to unravel when new employee Darlene scoffs at her weekend baking business and steals her best friend Holly and the attentions of her chemistry partner, but she sees redemption at hand when she gets a chance to meet sexy celebrity baker Lorenzo LaRue and realizes she should continue to chase her dreams.